KONSEP NEGARA DALAM FILSAFAT POLITIK AL-FARABI DAN KONTEKSTUALISASINYA DI INDONESIA - Umi Samsiyah (UIN Sunan Kalijaga Yogyakarta, 2021)
This article describes the concept of the state promoted by al-Farabi and its contextualization with politics in Indonesia.This discussion is interesting because there are several values in al-Farabi's thought that can be contextualized with the political system in Indonesia.For this reason, this article carries two problem formulations, namely how is the concept of the state promoted by al-Farabi?How is the contextualization of al-Farabi's concept of state with the political system in Indonesia?By using a literature review, this article finds that al-Farabi's thoughts are a combination of his reading of Plato's and Aristotle's thoughts with Islamic religious doctrines.Al-Farabi constructs an ideal state form in which there are good people and leaders who aim to achieve happiness.The Indonesian state in al-Farabi's country classification can be equated with al-Farabi's democratic state,namely there are some similarities with the Pancasila democratic system which is the Indonesian state administration system.